Radiological risk assessment of some consumed cigarettes and hookah in Iraq - Amin, Sahar; Haleem, Azhar; Mahmood, Ola (International Journal of Physical Research, 2020)
The main purposes of the research are to assess the radiological risk due to smoking cigarettes and hookah and their impacts on the people health. Radon levels were measured in 28 consumed brands of cigarettes and 10 brands of hookah consumed Iraq using CR-39 solid state nuclear track detectors (SSNTDs). The results showed that the 222Rn concentration in cigarette tobacco samples ranged from 138.9 to 781.2 Bqm-3 with average value of 318.0 Bqm-3. The radon concentrations emerged from 11brands of the investigated samples was significantly higher than the recommended value. While, its concentration in hookah ranged from 633.6 Bqm-3 to 416.6 Bqm-3 with average value of 509.5 Bqm-3. The Potential Alpha Energy Concentration (PAEC) in terms of (WL) units, Exposure to radon progeny (EP), and the annual effective dose (AED) in terms of (mSv/y) units were also obtained. Lung cancer cases per year per million people (CPPP) are also evaluated with an average value of 144.4 per million people. The result indicates that the average values of PAEC, EP and AED were within the recommended range values given by UNSCEAR, NCRP and ICRP respectively. The radioactive impact of smoking is considered as a risk factor for lung cancer.